Improved optical and mechanical characteristics of multilayered Cu/TiON/CrO2 coating via heat treatment for solar absorbing applications - Taha, Hatem; Al-Azzawi, Sawsan; M Mahbubur Rahman (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In the last few decades, growing interest has been shown in the development of new solar selective coatings based on transition metal nitride and/or oxinitride for solar absorbing applications. Solar thermal collectors are well thought out to be the most effective process of converting and harvesting solar radiation. In this investigation, Cu/TiON/CrO2 multilayered solar selective absorber coatings have been coated onto Al substrates using the dip-coating process followed by an annealing process at (400, 450, 500, 550, and 600 °C. The XRD analysis showed excellent crystalline quality for the prepared thin films along with enhanced surface features as proved by FESEM images, and the grains are in the range of (27–81) nm. The optical investigations revealed that the film annealed at 600 °C exhibits improved solar absorptance, thermal emittance, and solar selectivity of  ~ (90.7 %), (5.8 %) and 15.6, respectively. Also, the highest values of hardness ~ (26.8 GPa) and Young’s modulus ~ (250 GPa) were assigned for the film annealed at the highest temperature. Calculated optical band gaps of fabricated thin multilayered Cu/TiON/CrO2 films were found to be in the range of (1.8 – 2.10) eV.